Formação inicial de professores de ciências: construção de saberes docentes com a linguagem de programação visual Scratch - Rocha, Helen Regiane Pará (Instituto Federal do Amazonas, 2018)
With the intention of knowing which teaching knowledge can be constructed by future teachers of Sciences in initial formation, from experiences with the use of the visual programming language Scratch, this research was developed in the context of the Licentiate course in Physics of the Institute Federal University of Education, Science and Technology of Amazonas (IFAM), Manaus Campus Center (CMC), there is no space of the discipline, with students enrolled in the 5th and 7th periods. Because it is a research with an effective participation of the subjects, it was chosen as methodological support, an action research, through the qualification is implemented as an investigative action, with a workshop called "Programming with the risk to learn Sciences", which It was configured as the product of this research for an initial formation of Science teachers. (2008), Resnick (2007, 2013, 2014), Valente (1999), and in particular; 2014), Prado (1996), Demo (2008) to deal with the context of computer programs as a proposal for insertion in school, as well as in teacher training; Later on with Tardif (2014), Carvalho and Gil Perez (2001), Pimenta (2008) and Costa (2012), among others, to approach as conceptions related to teaching knowledge. The collected data were treated by discursive textual analysis (MORAES, GALIAZZI, 2011). As conclusions of the research on the infer that there was a construction of knowledge of experience and knowledge, and that are known as convergent for the construction of pedagogical knowledge in the initial formation of science teachers.